DIFFERENCE BETWEEN THEORETICAL AND DESCRIPTIVE LINGUISTICS - Talibjanova Aziza Lutfullayevna; Sabirova Nafisa Qurolbayevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article aims to explain the difference between theoretical and descriptive linguistics. Theoretical linguistics deals with the study of language as a universal phenomenon, while descriptive linguistics focuses on the study of particular languages and their structures. The article highlights the methods used in each approach, provides examples, and presents the findings of the research. The article concludes by discussing the importance of both approaches and suggesting future research directions.